THE DIDACTIC MODEL OF ACTIVATING STUDENTS’ INDEPENDENT WORK (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article dip lays a didactic model of designing educational activities to activate the requirements of independent learning on the example of general subjects.  It also shows the pedagogical process, the pedagogical system and its stages, algorithms of educational activities, didactic materials that are needed to activate the independent learning of students.